Multi-Scale Intersections of Collaborative Collective Actions in Urban Regeneration: Insights from the ROCK project in Lisbon - Falanga, Roberto (2019)
Collective collaboration between NGOs, associated and non-associated agents can capitalise knowledge, experience and expertise in initiatives for social change. This contribution focusses on forms of citizen engagement funded by international and local agencies for urban regeneration. Focus on the city of Lisbon allows to shed light on the multi-scale intersections between the international project “ROCK - Regeneration and Optimisation of Cultural heritage in creative and Knowledge cities” funded by the European Commission, and the programme for urban regeneration “BIPZIP - Bairros de Intervenção Prioritária Zonas de Intervenção Prioritária” promoted by the municipality of Lisbon. The international project and the local programme aim to engage foster collective collaborative actions for urban regeneration, with cultural heritage as the main driver in the ROCK project and socio-territorial cohesion as the core issue in the BIPZIP programme. Zooming in on the specific urban area of intervention between Marvila and Beato neighbourhoods, this contribution retrieves some inputs from the empirical knowledge collected within the ongoing research conducted by the authors in Lisbon. We argue that the lack of an integrated management between the project and the programme can be considered as emerging burdens due to limited multi-scale intersections between the project and the programme.